The Effect of Lunar Elongation and Illumination Fraction on the Visibility of the Moon - Mazratul Aini mazra; Arino Bemi Sado (Universitas Islam Negeri Mataram, 2024)
The visibility of the new Moon is significantly influenced by the Sun’s position at Sunset, often referred to as elongation or the angular distance between the Sun and Moon. The criteria currently agreed upon by the Indonesian government for determining the start of the lunar month are the NEW-MABIMS criteria, which require a minimum Moon height of 3° and a minimum crescent elongation of 6,4°. This thesis aims to (1) determine the influence of elongation and lunar illumination fraction on the visibility of the new Moon, and (2) identify the elongation value and lunar illumination fraction that impact the new Moon’s visibility at Loang Baloq Beach. This research employs a field research method using a mixed-methods approach. Data collection methods include observation and documentation. The result of this thesis indicates that (1) both elongation and lunar position fraction affect the visibility of the new Moon. Multiple linear regression analysis, a correlation value of 68,41%, categorized as strong, a coefficient value of 41,96%, categorized as moderate and R2 46,8% also categorized as moderate. This suggests a significant influence of elongation and lunar illumination fraction on the visibility of the crescent Moon, though other factors also contribute. (2) the smallest crescent observed was at the elongation of 8° 11’ 24.00” with an illumination fraction of 0,69%. This record serves as the minimum elongation and illumination fraction values impacting new Moon visibility at Loang Baloq Beach over the last three years. In general, the greater the elongation, the larger the illumination fraction, indicating that as the Sun’s distance from the Moon increases, the visibility of the illuminated portion of the Moon also increases.